Pengkajian Penerapan Prinsip Iktikad Tidak Baik dalam Pendaftaran Merek pada Sengketa Merek “C+Logo” - Lucia Samosir; Rika Ratna Permata; Aam Suryamah (International Forum of Researchers and Lecturers, 2025)
The advancement of information technology has driven the growth of the creative industry, which heavily relies on intellectual works, one of which is trademarks as part of the Intellectual Property Rights regime. A trademark not only serves as a product identity but also as a marketing tool and a determinant of reputation. However, in practice, legal issues often arise, particularly related to the registration of trademarks by parties acting in bad faith and having substantial similarities with previously registered trademarks. This research analyzes the Application of the Principle of Bad Faith in the trademark registration process in the trademark dispute